African musical aesthetics - Murungi, John, 1943- (Cambridge Scholars, 2011)
In the West, philosophy is generally confined to the domain of the intellect, and music to the domain of the emotion. This book makes either domain the location for the other. African musical aesthetics constitutes this location, and has its home in it. Moreover, since the separation of the domain of the intellect and the domain of emotion represents a bifurcation of what it is to be a human being, and by making either domain the location of the other, what African musical aesthetics accomplishes is the affirmation of a unified sense of what it is to be a human being. Accordingly, the unity of philosophy and music give rises to a unified sense of being human. It is to such unity that African musical aesthetics takes us.